2008
DOI: 10.1002/jsfa.3243
|View full text |Cite
|
Sign up to set email alerts
|

The effect of irrigation level and harvest mechanization on virgin olive oil quality in a traditional rain‐fed ‘Souri’ olive orchard converted to irrigation

Abstract: BACKGROUND: Olive trees are generally grown under rain-fed conditions. Since yield response to application of water in the growing season may be considerable, irrigation is increasingly introduced to existing, mature orchards. An additional feature of modernization of olive cultivation is mechanical harvesting. To investigate the effect of irrigation level on the quality of virgin olive oil (VOO) produced from cv. Souri, six regimes, ranging from deficit to excess, were applied to trees in a mature, traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 64 publications
(116 reference statements)
3
62
5
2
Order By: Relevance
“…In fact, a sufficient irrigation of the grove, an early harvest of the fruits, a non-stressful olive pressing, a reduced temperature and a more prolonged kneading phase should be adopted to produce an oil characterized by a high content of volatile components and by a more pronounced aroma as well (Dag et al, 2008). To increase the phenolic fraction and then to produce an oil characterized by greater bitterness and stability, it is necessary to ensure a reduced irrigation of the olive trees, the utilization of less ripe fruits, the use of more efficient crushers able to break also the pit and a kneading phase carried on at a higher temperature for a reduced time.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a sufficient irrigation of the grove, an early harvest of the fruits, a non-stressful olive pressing, a reduced temperature and a more prolonged kneading phase should be adopted to produce an oil characterized by a high content of volatile components and by a more pronounced aroma as well (Dag et al, 2008). To increase the phenolic fraction and then to produce an oil characterized by greater bitterness and stability, it is necessary to ensure a reduced irrigation of the olive trees, the utilization of less ripe fruits, the use of more efficient crushers able to break also the pit and a kneading phase carried on at a higher temperature for a reduced time.…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation is highly effective in increasing yield and yield components such as fruit size, fruit number and oil content, moreover, irrigation affects the pulp-to-pit ratio, phenology and time of fruit maturation (Agabbio, 1978;Goldhamer et al, 1994;Michelakis et al, 1994;Inglese et al, 1996;Gòmez-Rico et al, 2006, 2007Dag et al, 2008;Servili et al, 2007).…”
Section: Irrigationmentioning
confidence: 99%
“…Increasing irrigation leads to fruits with a greater water content (lower oil percentage), and irrigation has been found to decrease the polyphenol content (Patumi et al, 1999;Gómez-Rico et al, 2006;Ben-Gal et al, 2008;Dag et al, 2008), which then changes the oil bitterness and spicy tastes.…”
Section: Olive Tree Water Needsmentioning
confidence: 99%
“…Although a number of studies have reported effects of irrigation on yield parameters under conditions and varieties, there is shortage of the influence of harvesting method on oil quality. [1], studied on the effects of irrigation on oil quality of fruit obtained from both mechanical and hand harvesting methods. They found that when fruit was picked carefully by hand so that no injuries were inflicted, free fatty acids levels were substantially reduced, peroxide was reduced and total polyphenol content was increased.…”
Section: Introductionmentioning
confidence: 99%